2017
DOI: 10.1140/epja/i2017-12240-7
|View full text |Cite
|
Sign up to set email alerts
|

Quartet correlations in N = Z nuclei induced by realistic two-body interactions

Abstract: Two variational quartet models previously employed in a treatment of pairing forces are extended to the case of a general two-body interaction. One model approximates the nuclear states as a condensate of identical quartets with angular momentum J = 0 and isospin T = 0 while the other let these quartets to be all different from each other. With these models we investigate the role of alpha-like quartet correlations both in the ground state and in the lowest J = 0, T = 0 excited states of even-even N = Z nuclei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…In all cases α g,J=0 turns out to be the largest amplitude. This is especially the case for 28 Si, which clearly stands out for a much more prominent role of this amplitude as compared with the J > 0 ones. We shall further comment on this point below.…”
Section: Procedures and Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…In all cases α g,J=0 turns out to be the largest amplitude. This is especially the case for 28 Si, which clearly stands out for a much more prominent role of this amplitude as compared with the J > 0 ones. We shall further comment on this point below.…”
Section: Procedures and Resultsmentioning
confidence: 64%
“…For what concerns 28 Si, what is most striking in the spectrum of Fig. 2(B) is the absence of a state 0 2 close to the state 4 1 as observed in both the shell model and the experimental spectrum.…”
Section: Procedures and Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In particular, as shown recently, the isovector plus isoscalar Hamiltonian (30) can be treated accurately in terms of alpha-like quartets built by two protons and two neutrons coupled to total isospin T = 0, rather than in terms of Cooper pairs [35]. It has also been shown that T = 0 alpha-like quartets are the main building blocks for systems governed by the general shell model Hamiltonian (33) [36][37][38]. These studies clearly show that 4-body correlations play a key role in the N=Z nuclei.…”
Section: Discussionmentioning
confidence: 98%
“…One of the questions under investigations is an existence of α-type condensate in the ground states of nuclei [9,10,11,12,13,14,15]. The Quartet Condensate Model was proposed for studing of the isovector pairing and quarteting correlations in N=Z nuclei [16,17,18,19,20,21,22,23]. The boson approximation technique has been applied to description of the pairing and quarteting correlations [24].…”
Section: Introductionmentioning
confidence: 99%